Penerapan Model Pembelajaran Berbasis Proyek (Project Basic Learning) Kompetensi Teknik Pemesinan Frais Sebagai Upaya Meningkatkan Hasil Belajar Siswa Kelas XI Teknik Pemesinan (TPM) SMK Negeri 1 Kalitengah Tahun Pelajaran 2019/2020 - Amin, Muhammad (MADINAH, 2019)
How can students not forget the subject matter that they have received so that students will be ready to face the exams that they are ready or not ready to face. How to make a teaching material so that it is not forgotten by students. In this case the teacher must find a method to remind all the memories in the minds of students that they have received. The teacher must be able to revive the memory. This research uses three rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is the students of class XI TPm SMK N 1 Kalitengah. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student achievement increased from cycle I to cycle III, namely, cycle I (73.33%), cycle II (83.33%), cycle III (93.33%). The conclusion of this study is that the project/task-based learning model can have a positive effect on the learning achievement of XI TPm Students of SMK N 1 Kalitengah, and this learning model can be used as an alternative to learning productive subjects.